The Effect of Integrating Intertidal Gastropod Diversity on Ecological Literacy and Professional Competence of Pre-Service Biology Teachers - Djalo, Aloysius; Missa, Hildegardis; Santos, Americo Dos (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2026)
The limited use of local environmental contexts in Invertebrate Zoology courses may reduce ecological literacy and professional competence among pre-service biology teachers. This study examined the effect of integrating intertidal gastropod biodiversity into course instruction on students’ ecological literacy and professional competence. A quasi-experimental pretest–posttest control group design was used with 58 pre-service teachers assigned to experimental and control groups. The experimental group participated in biodiversity-based contextual learning using authentic field data, while the control group received conventional instruction. Data were collected through validated ecological literacy and professional competence tests and analyzed using N-Gain and analysis of variance (ANOVA). The experimental group achieved a higher N-Gain score (0.73, high category) than the control group (0.51, moderate category). ANOVA showed a significant effect on posttest scores (p < 0.001) with a large effect size (Partial η² = 0.311). These findings indicate that authentic biodiversity-based learning enhances ecological understanding and professional competence. Pengaruh Integrasi Keanekaragaman Gastropoda pada Zona Intertidal terhadap Literasi Ekologi dan Kompetensi Profesional Mahasiswa Calon Guru Biologi ABSTRAK: Terbatasnya penggunaan konteks lingkungan lokal dalam mata kuliah Zoologi Invertebrata dapat mengurangi literasi ekologi dan kompetensi profesional calon guru biologi. Penelitian ini mengkaji pengaruh integrasi keanekaragaman gastropoda intertidal dalam pembelajaran terhadap literasi ekologi dan kompetensi profesional mahasiswa. Penelitian ini menggunakan desain kuasi eksperimen dengan pola pretest–posttest control group yang melibatkan 58 calon guru, yang dibagi ke dalam kelompok eksperimen dan kelompok kontrol. Kelompok eksperimen mengikuti pembelajaran kontekstual berbasis keanekaragaman hayati menggunakan data lapangan autentik, sedangkan kelompok kontrol memperoleh pembelajaran konvensional. Data dikumpulkan melalui tes literasi ekologi dan kompetensi profesional yang telah divalidasi, kemudian dianalisis menggunakan N-Gain dan analysis of variance (ANOVA). Kelompok eksperimen memperoleh skor N-Gain lebih tinggi (0,73; kategori tinggi) dibandingkan kelompok kontrol (0,51; kategori sedang). Hasil ANOVA menunjukkan pengaruh signifikan terhadap skor posttest (p < 0,001) dengan effect size besar (Partial η² = 0,311). Temuan ini menunjukkan bahwa pembelajaran autentik berbasis keanekaragaman hayati dapat meningkatkan pemahaman ekologi dan kompetensi profesional.